Outbound games to enhance children’s social skills - Pratiwi, Anatasya Ristu; Mashar, Riana; Puspitasari, Intan; Hastuti, Dwi (Universitas Ahmad Dahlan, 2023)
Social skills play an important role in the academic and social success of early childhood, but teachers are not stimulated optimally. This study investigated the impact of outbound games on the social skills of group B (5-6 years old) at TK ABA Karangkunti. A pretest-posttest design was used with a sample of 10 children. Social skills data were gathered using an observation guide with an interval scale. The experimental treatment involved 10 outbound games, and data from pretests and posttests were analyzed using the Wilcoxon technique in SPSS. This study found that outbound games can improve the social skills of children at TK ABA Karangkunti, suggesting that this method is effective. However, the study is limited by a small sample size and specific context. Further research with a broader scope is recommended to validate these results and examine the long-term effects of outbound games on children's social skills.